Pleiotropic action of genetic variation in ZNF804A on brain structure: a meta-analysis of magnetic resonance imaging studies - Wang S (Dove Medical Press, 2019)
Shuai Wang,1,2 Yi He,3 Zi Chen,1 Yanzhang Li,1 Jingping Zhao,2 Luxian Lyu4 1Department of Psychology, Chengdu Medical College, Chengdu, People’s Republic of China; 2Mental Health Institute of the Second Xiangya Hospital, Central South University, National Clinical Research Center on Mental Health Disorders, National Technology Institute on Mental Disorders, Hunan Key Laboratory of Psychiatry and Mental Health, Changsha, People’s Republic of China; 3Medical Group, Department of Academic Popularization, DIAO Group, Chengdu, People’s Republic of China; 4Henan Mental Hospital, The Second Affiliated Hospital of Xinxiang Medical University, Xinxiang, People’s Republic of China Objective: The zinc finger protein 804A (ZNF804A) gene encodes the protein 804A containing the C2H2 zinc finger structure, which plays an important role in embryonic nerve development and repair. Previous studies have shown a significant association between the ZNF804A genetic variation polymorphism rs1344706 and the risk of schizophrenia and brain structure abnormalities. However, the findings are inconsistent. Materials and methods: Seventeen studies on structural magnetic resonance imaging (sMRI), with 1,031 schizophrenia patients and 3,416 healthy controls, were included in the meta-analysis. These analyses were performed using Anisotropic Effect-Size Signed Differential Mapping (AES-SDM) software and Comprehensive Meta-Analysis (CMA) software. Results: rs1344706 risk allele carriers of schizophrenia had increased gray matter in the brain regions including frontal lobe, temporal lobe, and other brain regions, but the carriers of healthy individuals had decreased gray matter and white matter integrity in the frontal lobe, central network, and other brain regions. The results of sensitivity analysis are stable, but publication bias exists in a few analyses of indexes. Conclusion: Abnormalities of brain structure have a strong relationship with ZNF804A gene rs1344706 polymorphism, but the association may be different in healthy individuals and those with mental disorders. Keywords: ZNF804A, genetic variation, magnetic resonance imaging, brain structure, meta-analysis